TREM2 shedding by cleavage at the H157‐S158 bond is accelerated for the Alzheimer's disease‐associated H157Y variant - Peter Thornton; Jean Sevalle; Michael J Deery; Graham Fraser; Ye Zhou; Sara Ståhl; Elske H Franssen; Roger B Dodd; Seema Qamar; Beatriz Gomez Perez‐Nievas; Louise SC Nicol; Susanna Eketjäll; et al. (EMBO Molecular Medicine)
Abstract We have characterised the proteolytic cleavage events responsible for the shedding of triggering receptor expressed on myeloid cells 2 (TREM2) from primary cultures of human macrophages, murine microglia and TREM2‐expressing human embryonic kidney (HEK293) cells. In all cell types, a soluble 17 kDa N‐terminal cleavage fragment was shed into the conditioned media in a constitutive process that is inhibited by G1254023X and metalloprotease inhibitors and siRNA targeting ADAM10. Inhibitors of serine proteases and matrix metalloproteinases 2/9, and ADAM17 siRNA did not block TREM2 shedding. Peptidomimetic protease inhibitors highlighted a possible cleavage site, and mass spectrometry confirmed that shedding occurred predominantly at the H157‐S158 peptide bond for both wild‐type and H157Y human TREM2 and for the wild‐type murine orthologue. Crucially, we also show that the Alzheimer's disease‐associated H157Y TREM2 variant was shed more rapidly than wild type from HEK293 cells, possibly by a novel, batimastat‐ and ADAM10‐siRNA‐independent, sheddase activity. These insights offer new therapeutic targets for modulating the innate immune response in Alzheimer's and other neurological diseases.